Aerial mapping using autonomous fixed-wing unmanned aerial vehicle - Tahar, Khairul Nizam (2012)
This paper demonstrates the performance of a fixed-wing unmanned aerial vehicle in mapping semi-undulated area. Current practices incur huge cost and time consuming. The aim of this study is to evaluate photogrammetric technique for mapping slope. Fixed-wing unmanned aerial vehicle (UAV) was employed as a tool for image acquisition at the height of 300m. This unit is a complete package that includes low cost digital camera, autonomous chip, global positioning system (GPS), gyro and electronic speed controller. This study was conducted at Skudai, Johor, which is located approximately at latitude 1°33'24.49"N and longitude 103°39'4.30"E. All the acquired images were processed using photogrammetric technique which comprise of aerial triangulation and bundle adjustment. There are two main photogrammetric products produced from this study known as digital orthophoto and digital elevation model (DEM). Both products were analyzed to determine accuracy of the results. Ground control points and check points were distributed randomly at the study area and all the points were established using GPS Real Time Kinematic (RTK) technique. Based on the results, it was found that root mean square error for slope analysis is +1.169m and length analysis is +0.259m.